2018
DOI: 10.1177/0959651818803165
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental validation of 1-degree-of-freedom impacting oscillator

Abstract: In this article, a mechanical 1-degree-of-freedom oscillator with harmonic forcing and impacts was analysed both numerically and experimentally. A special attention was paid to the mathematical modelling and realistic numerical simulations of a real system. The developed experimental rig consists of a cart mounted on a guide, connected with springs to the support, and equipped with one-sided stiff limiter of motion. The cart was excited by an unbalanced disc mounted on the shaft of a stepper motor. Modelling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
(71 reference statements)
0
27
0
Order By: Relevance
“…For studies let us chose the case at ω = 40.86 rad/s (period 0.154). Recall [20] that the trajectory after some transition time leads to the chaotic attractor, the phase portrait of which is depicted in Fig. 6a.…”
Section: Chaotic Regimementioning
confidence: 99%
See 4 more Smart Citations
“…For studies let us chose the case at ω = 40.86 rad/s (period 0.154). Recall [20] that the trajectory after some transition time leads to the chaotic attractor, the phase portrait of which is depicted in Fig. 6a.…”
Section: Chaotic Regimementioning
confidence: 99%
“…The base of our studies is the dynamical regimes observed at the experimental rig comprising an impacting oscillator. Since the detailed discussion of this rig can be found in the paper [20], we give the short description only. The experimental stand corresponding to the physical model presented in Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations